Как мне тебя назвать? Статус глагольных энклитик в текстах русских летописей - Györfi, Beáta (SlavVaria, 2022)
What Should I Call You? The Status of Verbal Enclitics in the Texts of the Russian Chronicles. The existence of verbal enclitics in the Old Russian language seems to be a controversial issue. The article offers an answer to the question posed in the title. A brief overview of the OR auxiliaries is given. After that, an overview of the universal features of enclitics is given. The grammatical properties of the auxiliaries in the texts of six chronicles are considered with the help of the Russian National Corpus.